Workplace spirituality and organizational citizenship behavior among teachers in bahrain: commitment as a mediator. Issue 3 (3rd July 2022) - Al-Mahdy, Yasser F. Hendawy; Emam, Mahmoud; Hassan, Tahani
ABSTRACT: The current study examined the mediating role of teacher commitment (TC) on the relationship between workplace spirituality (WS) and organisational citizenship behaviour (OCB) in Bahraini public schools. A cross-sectional survey design was used to examine a proposed conceptual model. Data were collected from 349 teachers in Bahraini public schools, and were analysed using structural equation modelling (SEM). The study found that workplace spirituality contributes to the teachers' OCB both directly and indirectly by shaping teachers' affective commitment. The study findings provide a framework that can assist policymakers and school principals in the enhancement of WS in schools in order to build and nurture a culture of OCB and ensure commitment, thereby improving school effectiveness.